Exploring Help-Seeking Behavior of Mildly Distressed Guidance and Counseling Practitioners: Basis for Program Development - Lipat, Diane D.; Espinol, Shara May T.; Camaclang, Kenneth; Manalo, Rosemarie Mayanne; Maranan, Carl Reman (Journal of Cultural Analysis and Social Change, 2026)
Mental health concerns are one of the top problems being faced globally. It can affect people regardless of economic status, educational background, profession, age, and gender. Challenges to mental health can be experienced by anyone and that includes mental health service providers such as counselors and counseling practitioners, psychologists, and therapists. This study aims to understand and explore the help seeking behavior of distressed counselors. Specifically, it sought to answer the following questions such as who the mildly distressed guidance and counseling practitioners are, what is the nature of the stress of the guidance and counseling practitioners, what is the help-seeking behavior of the mildly distressed guidance and counseling practitioners and what output may be proposed based on the overall results of the study. The study used qualitative research design, specifically case study and focused on 5 guidance and counseling practitioners in CALABARZON area who were selected purposively. Data gathered were analyzed through thematic analysis and cross case analysis. Ethical considerations were also given emphasis during the conduct of the study. Results showed that guidance and counseling practitioners of varying profiles experience mild distress and have difficulty seeking professional help. Guidance and counseling jobs contribute to their distress. Also, guidance and counseling practitioners have difficulty seeking help. There is a need for a program that contains discussion on mental health importance, nature of counseling profession and stress management activities and personal therapy to be included in the institutional training and personal development programs offered once or twice a year by the institution for its guidance and counseling practitioners. It is also recommended that guidance and counseling practitioners may engage themselves in activities that promote their own mental health welfare and may attend more training that helps them be more equipped in handling negativities in life that can affect their personal and professional life. Human resource department and the institution should work with different professionals who will serve as external counselors and facilitate training or conduct seminars and counseling and therapy for guidance and counseling practitioners to promote mental health. Future researchers may consider other mental health practitioners as participants to determine the way they perceived and experienced distress and how it influenced their lives as professionals.